The Impact of Intrinsic Religiosity on Consumers' Ethical Beliefs: Does It Depend on the Type of Religion? A Comparison of Christian and Moslem Consumers in Germany and Turkey - BAYRAKTAR, AZRA (SPRINGER, 2011)
Intrinsic religiosity drives ethical consumer behavior; however, previous studies regarding this connection are limited solely to a Christian cultural context. This comparative study instead includes Christian Consumers from Germany and Moslem Consumers from Turkey to determine if a specific religious community moderates the connection between intrinsic religiosity and consumer ethics. The results show that Consumers in the Turkish, Moslem subsample, exhibit an even stronger connection between religiosity and ethical consumer behavior than Consumers from the German, Christian subsample.
Keywords: religiosity; consumer ethics; Islam; religion; Christianity; MARKETING ETHICS; DECISION-MAKING; BUSINESS ETHICS; FINAL CONSUMER; ORGANIZATIONS; PERSONALITY; PERSPECTIVE; JUDGMENTS; COUNTRIES; ATTITUDES